Towards More Choice in Social Protection? Individual Choice of Insurer in Basic Mandatory Health Insurance in Switzerland - Colombo, Francesca (OECD Labour Market and Social Policy Occasional Papers, 2001)
There is a considerable interest in some OECD countries in understanding how greater choice in health markets can be combined with the equity and efficiency goals of health systems. This paper reviews the system of free choice of insurer in basic mandatory health insurance that was introduced in Switzerland with the 1994 Health Insurance Law (LAMal). The thrust of the reform was to increase solidarity in basic health insurance while enhancing choice among individuals and competition on quality-price ratios among insurers. The reform encompassed regulatory mechanisms to facilitate the switching mechanism and choice-led competition, such as measures to ensure cross-subsidisation across individuals of different risk and income, information disclosure requirements for insurers, and the mandatory participation to a risk equalisation mechanism for all insurers offering basic health insurance. The analysis presented in this paper suggests that some features of the individual choice ...